Large-time behavior of smooth solutions to the isothermal compressible fluid models of Korteweg type with large initial data. (October 2016) - Chen, Zhengzheng
Abstract: This paper is concerned with the large-time behavior of smooth non-vacuum solutions with large initial data to the Cauchy problem of the one-dimensional isothermal compressible fluid models of Korteweg type with the viscosity coefficient μ ( ρ ) = ρ α and the capillarity coefficient κ ( ρ ) = ρ β . Here α ∈ R and β ∈ R are some parameters. Depending on whether the far-fields of the initial data are the same or not, we prove that the corresponding Cauchy problem admits a unique global smooth solution which tends to constant states or rarefaction waves respectively, as time goes to infinity, provided that α and β satisfy some conditions. Note that the initial perturbation can be arbitrarily large. The proofs are given by the elementary energy method and Kanel's technique (Kanel, 1968). Compared with former results in this direction obtained by Germain and LeFloch (2016), and Chen et al. (2015), the main novelties of this paper lie in the following: First, we obtain the global existence of smooth solutions with large data for some new varieties of parameters α and β . Second, the large-time behavior of smooth large solutions around constant states is established.